Strategi Guru Pendidikan Agama Islam Dalam Menanamkan Karakter Islami - Hafidz Zaldi; Rengga Satria (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the strategies of PAI teachers and the supporting and inhibiting factors in instilling Islamic character in SD Negeri 41 Seberang Padang Selatan. This study uses a qualitative method with the type of research Library Research (library research). Sources of research data are principals, PAI teachers, homeroom teachers, and several students. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the strategies of PAI teachers in instilling Islamic character in SD Negeri 41 Seberang Padang Selatan were exemplary strategies, advice, habituation, and innovative learning. The results of this study also show that the supporting factors in instilling Islamic character in SD Negeri 41 Seberang Padang Selatan are professional teachers and the school environment, while the inhibiting factors in instilling Islamic character in SD Negeri 41 Seberang Padang Selatan are the parent factor and the gadget factor.